A cohort study of the prevalence of sleep problems in adults with intellectual disabilities. - Boyle, A; Melville, C; Morrison, J; Allan, L; Smiley, E; Espie, C; Cooper, SA (2010)
Previous studies of the prevalence of sleep problems in adults with intellectual disabilities (ID) are affected by small, potentially biased samples and other limitations. This study aims to determine the prevalence and associations of sleep problems in the adult population with ID. The 4-week period prevalence of sleep problems was determined in a cross-sectional study of all adults with ID in a defined geographical area. Sleep problems were identified using the Psychiatric Assessment Scale for Adults with Developmental Disabilities (PAS-ADD) checklist and categorized as initial insomnia, early morning wakening and broken sleep. A fourth, composite, variable of significant sleep problem was also derived. Of the 1023 adults with ID who participated, 9.2% had experienced a significant sleep problem, during the 1-month period. Individuals with a significant sleep problem are more likely to have mental ill-health [odds ratio (OR) = 5.53, 95% confidence interval (CI) 3.52-8.69], problem behaviours (OR = 2.06, 95% CI: 1.25-3.41) and respiratory disease (OR = 2.03, 95% CI: 1.27-3.26). There is a positive association between visual impairment and initial insomnia (OR = 1.91, 95% CI: 1.21-3.04). Although a diagnosis of epilepsy is not associated with sleep problems, the finding that individuals taking antiepileptic medication are more likely to experience broken sleep (OR = 1.73, 95% CI: 1.13-2.66) suggests that medication side effects may impact on sleep of individuals with ID. The results suggest that there is a need to further examine the relationship between sleep problems and co-morbid health problems, which would inform the development of interventions, and trials of their efficacy.